PENGARUH WAKTU POLISHING DAN ASAM SITRAT TERHADAP MICROLEAKAGE PADA TUMPATAN RESIN KOMPOSIT NANOFILLER AKTIVASI LIGHT EMITING DIODE - In Vitro - Dhurohmah .; Rochman Mujayanto; Siti Chumaeroh (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: The objective of this research is to investigate influence of polishing time and citric acid on microleakage in nanofiller composite resin restoration (Z350XT,3M). Method: The research was conducted on a class V restoration amount sample 24 on bovine teeth. The first group restoration was polished immediately after curing then was soaked in distilled water. The second group was polished immediately after curing and then was soaked in citric acid.The third group was polished after 24 hours of curing and then was soaked in distilled water. The fourth group was polished after 24 hours of curing then was soaked in citric acid. Samples were immersed for 7 days and then were soaked in methylene blue for 1 day and were split longitudinally and were observed using microskopstereo and were measured using calipers. Result: Data were analized by Kruskal-wallis with the result of p > 0,05, there is a significant difference in group I, II, III, and IV. Mann- Whitney test results the difference between the data. Conclusion: The conclution is there were significant differences between the groups which immersed with citric acid of distilled water and there is no significant difference between groups which polished immediately and polished 24 hours later.